Sobre la convexidad de la función de presión en el problema de la filtración no lineal - Grebenev, Vladimir N. (1998)
We prove the convexity of the pressure function v for the isotropic ideal gaz flow, based on the theorem about the zeros of the solution of the parabolic equation (1)